Dampak Eksternalitas Peternakan Kambing Perah terhadap Kehidupan Masyarakat Sekitar - Cyrilla, L.; Salundik, Salundik; Muhasibi, H. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
The number of milk consumption 12.50 Ls capita-1 year-1 have not been able to be  met through  national milk  production. Deficit in milk production opportunities for dairy goat farmers to develop the business. Livestock development resulting externalities.  According to Pindyck, Robert and Rubinfeld (2007) An externality is an activity either by perodusen or consumers that can affect producers and other consumers, but not factored into the cost of the market. Indirectly these impacts will be considered for the  development of dairy goat farming business, so the need for studies on the impact of positive and negative externalities caused by the presence of dairy goat farm. The purpose of this study was to analyze the impact of dairy goat farm externalities on people's lives around. The experiment was conducted at Wake Karso dairy goat farm. The population in this study is the community living around the dairy goat farm. Sampling method used was purposive sampling. This study uses 70 respondents who dwelt at a distance of 0 to 1 km from dairy goat farms. The results showed that the majority of people (57.32%) expressed disagreement to the positive externalities generated and the majority of people (90.20%) expressed disagreement to the negative externalities caused. Positive externalities not provide a real benefit to society and the negative impacts are not felt by the public, so the public is not compromised states due to dairy goat farm.